PENINGKATAN KUALITAS PELAYANAN PUBLIK MELALUI PROGRAM ONE AGENCY ONE INNOVATION DI KANTOR SEKRETARIAT DAERAH KABUPATEN ENREKANG - Rahmasari, Esar; Haerana, Haerana; Riskasari, Riskasari (Universitas Muhammadiyah Makassar, 2022)
The aim of the study was to determine the Improvement of the Quality of Public Services through the One Agency One Innovation Program with online/digital-based administrative services at the Regional Secretariat Office of Enrekang Regency. This type of research uses qualitative research. The results show that Improving the Quality of Public Services through the One Agency One Innovation Program in Enrekang Regency from aspects 1) The dimension of direct evidence with the existence of One Agency One innovation is that Special SEKDA of Erekang Regency makes online/digital-based service innovations in administrative services, 2) The reliability dimension of digital-based administrative services prepares reliable operator services because they have attended a lot of training. 3) The responsiveness dimension is a fast response but sometimes there are urgent matters that must be served quickly but usually there are network constraints or service queues. 4) The dimensions of the estimated service response guarantee that occurred during the one agency one innovation at the Enrekang Regency SEKDA office required 1 x 24 hour response. (5) The dimension of empathy in digital/online-based administrative services does not forget the previous culture, namely the 3S service culture, namely Smile, Greet and Greeting.